2015
DOI: 10.1189/jlb.3vmr0415-142r
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40/CHI3L1 drives inflammation on the road of tumor progression

Abstract: Inflammation plays a vital role at different stages of tumor progression. The development of tumors is affected by inflammatory mediators produced by the tumor and the host. YKL-40/chitinase-3-like-1 protein is often upregulated in inflammation-associated diseases. With the use of chronic inflammatory disease systems, we describe the role of YKL-40/chitinase-3-like-1 protein in enhancing the inflammatory response and its implications in tumorigenesis. We also discuss how pre-existing inflammation enhances tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 65 publications
(92 reference statements)
1
63
0
Order By: Relevance
“…Chitinase 3-like 1 (CHI3L1) is a member of the glycosyl hydrolase 18 family. CHI3L1 is considered to serve a role in the process of inflammation and tissue remodeling (34). A previous study demonstrated the association of high serum CHI3L1 expression level with poor patient prognosis and short survival time in human solid tumors, including lung cancer and liver cancer (35).…”
Section: Discussionmentioning
confidence: 99%
“…Chitinase 3-like 1 (CHI3L1) is a member of the glycosyl hydrolase 18 family. CHI3L1 is considered to serve a role in the process of inflammation and tissue remodeling (34). A previous study demonstrated the association of high serum CHI3L1 expression level with poor patient prognosis and short survival time in human solid tumors, including lung cancer and liver cancer (35).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data reveals that CLPs play a role in the progression of different types of cancer. Elevated levels of circulating YKL-40 are related to poor outcome or short diseasefree survival in glioblastoma, melanoma, ovarian, breast, colon, lung, and prostate cancers in humans (52,(84)(85)(86)(87)(88)(89)(90)(91)(92). Moreover, in breast cancer, elevated serum levels of YKL-40 have been used as a prognostic biomarker (84).…”
Section: Chitinase-like Proteins In Cancermentioning
confidence: 99%
“…For example, YKL-40 gene silence such as shRNA can abrogate tumor growth and angiogenesis [2]. Dr. V. Iragavarapu-Charyulu group employed chitin, a YKL-40 binding ligand, in breast cancer transplanted mice and interestingly found that chitin can protect cancer cells from lung metastasis [5], supporting the notion that competitive binding at YKL-40 heparin-binding motif is an alternative approach to attenuating YKL-40-mediated cancer dissemination. To provide immunotherapeutic value, we recently created a mouse-derived neutralizing antibody against YKL-40 that displays the ability to bind YKL-40 functional domain, thus ablating tumor angiogenesis [4].…”
mentioning
confidence: 94%